Studies on cultural morphological and pathogenic variability in isolates of Fusarium udum causing wilt of pigeonpea - and J.P. UPADHYAY, SANJEEV KUMAR* (Indian Phytopathology, 2014)
The present investigation was undertaken to study the cultural, morphological and pathogenic variability in fifteen isolates of Fusarium udum causal agent of pigeonpea wilt. The isolates were procured from four major pigeonpea growing states, Bihar, Jharkhand, Orissa and West Bengal. These exhibited considerable variations in cultural and morphological characters on potato dextrose agar medium. The colony diameter ranged from 29.6 to 57.3 mm after eight days of incubation at 27±2°c. Six isolates produced white mycelia color, serrated margin with fluffy growth with light and dark yellow pigmentation while four isolates produced white mycelia color, serrated margin with partially appressed growth with dark yellow to brown pigmentation in substrate. Remaining five isolates produced white mycelia color, serrated margin with appressed growth with light yellow to brown pigmentation. The dry mycelium weight ranged from 98.3 to 201.0 mg, while number of spore ranged from 0.8 to 3.6 million ml_1 from potato dextrose broth medium after 15 days at 27±2°c. The size of macro conidia and micro conidia ranged from 15.4-45.0 X 2.1-6.2 µm and 2.5-17.5 X 2.1-6.2 µm, respectively. Pathogenic variability on soil inoculated pot grown plants of pigeonpea resulted in 0.0 to 42.3 percent wilt incidence. Based on the wilt incidence, the fifteen isolates were distinguished into pathogenic groups, where isolates Fu-37, Fu-61 and Fu-80 were found highly pathogenic. Isolates Fu-8 did not induce wilting and appeared non pathogenic.